ПОЛІСТИЛІСТИЧНА МОДЕЛЬ СВІТУ В. СТУСА (В АСПЕКТІ КАТЕГОРІЇ ГАРМОНІЙНОГО ) (Педагогіка вищої та середньої школи, 2002)
The symbolic process of the national self-identification of a personality through a polystylistic model of the world in the aspect of harmonious category on the material of V.Stus's poetry of the 70-80ies is investigated.